Efficacy of instability resistance training - Cowley, P. M.; Swensen, T.; Sforzo, G. A. (International Journal of Sports Medicine, 2007)
The use of the stability ball as a platform for upper-body resistance training has gained much attention in recent years. However, the efficacy of such training regimens remains largely unstudied. The purpose of this study was to evaluate the influence of platform (unstable vs. stable, stability ball vs. flat bench) on strength and work capacity during barbell chest-press exercise. We also sought to determine the effects of a barbell chest-press training program performed on a stability ball or flat bench on strength, work capacity, and abdominal power. Fourteen young women (20 - 23 yr) performed a 1 repetition maximum (1RM) barbell chest-press and the YMCA bench press test (YBT) on a stability ball and flat bench, as well as two field tests measuring abdominal power. The women were then assigned to perform 3 weeks of barbell chest-press training on a stability ball (SB group) or flat bench (FB group); assignment was balanced based on 1RM strength. Barbell chest-press training included 3 sets of 3 - 5 repetitions at loads greater or equal to 85 % of 1RM. The 1RM barbell chest-press, YBT, front abdominal power test (FAPT), and side abdominal power test (SAPT) were used to evaluate changes in strength, work capacity, and abdominal power, respectively. The chest-press tests were completed on both platforms following the training program. Platform (stability ball vs. flat bench) had no influence on strength, but work capacity was initially 12 % lower on the stability ball compared to the flat bench. In response to training, both groups significantly increased strength and work capacity, and there were no group differences. The increase in 1RM strength was 15 % and 16 % on the stability ball and flat bench for the SB group, and 16 % and 19 % for the FB group, respectively. The increase in work capacity was 32 % and 13 % on the stability ball and flat bench for the SB group, and 27 % and 26 % for the FB group, respectively. Both groups significantly improved on the FAPT, and there were no group differences. Performance on the FAPT improved by 5 % for the SB group, and 22 % for the FB group. Performance on the SAPT did not change. Barbell chest-press training performed on either the stability ball or flat bench increased strength and work capacity, and these changes were transferable across platforms. Thus, the stability ball is an effective platform for barbell chest-press training in untrained women over a short duration.